2013
DOI: 10.1021/cg3014688
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Networks Created by Charge-Assisted Hydrogen Bonding in Carboxylate Salts of a Bis(amidine)

Abstract: Amidines can be protonated by carboxylic acids to give amidinium carboxylates, and the ions can associate by forming multiple charge-assisted hydrogen bonds according to reliable motifs. Extended hydrogen-bonded networks can be constructed by treating suitable bis(amidines) with acids containing multiple carboxyl groups. To further explore the potential of this strategy, we have determined the structures of salts produced by treating 2,2′-bi-2-imidazoline, a cyclic bis(amidine), with oxalic, fumaric, terephtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In their work, dicationic bis(amidine) analogues were deliberately selected as hydrogen bonding donors, which was able to complex with anionic species, including phosphonate, sulfonate, or carboxylate compounds. However, single crystals revealed that nearly all resulting crystalline geometries were indeed no porous even though hydrogen bonding interactions were significantly enhanced [ 98 , 99 ]. What’s more, it was found that the charge-assisted hydrogen bonding protocol can be exploited in the fabrication of functionalized supramolecular copolymers [ 100 , 101 ].…”
Section: The Main Content Of This Reviewmentioning
confidence: 99%
“…In their work, dicationic bis(amidine) analogues were deliberately selected as hydrogen bonding donors, which was able to complex with anionic species, including phosphonate, sulfonate, or carboxylate compounds. However, single crystals revealed that nearly all resulting crystalline geometries were indeed no porous even though hydrogen bonding interactions were significantly enhanced [ 98 , 99 ]. What’s more, it was found that the charge-assisted hydrogen bonding protocol can be exploited in the fabrication of functionalized supramolecular copolymers [ 100 , 101 ].…”
Section: The Main Content Of This Reviewmentioning
confidence: 99%
“…The average C-C and C-N bond length values agree with those found in previously reported salts containing this monoprotonated organic cation. [64][65][66][67][68] In Figure 6 and Table 3). As seen in 1, short Cl···Cl contacts of 3.507(1) Å [Cl(4)···Cl(4a), (a) = -x+2, -y+1, -z+1] and 3.987(1) Å [Cl(1)···Cl(1b), (b) = -x+2, -y+1, -z+2] between [ReCl4(ox)] 2anions direct anionic chains, which grow along the crystallographic c axis (see Fig.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Amidines are an important class of compounds that are found throughout nature and have many uses in organic chemistry . Consequently, a number of useful and facile methods have been developed for the preparation of amidines, being able to synthetically incorporate amidine functionality to polymers .…”
Section: Introductionmentioning
confidence: 99%